Linking Transformational Leadership to OCB in Hospitality Industry: the Mediating Influence of Affective Commitment and Work Engagement - Istiqomah, Suryandari; Riani, Asri Laksmi (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2021)
This paper aims to examine the process of forming the Organizational Citizenship Behavior (OCB) of employees in the hotel industry. This study also uses affective commitment and work engagement as mediating variables to clarify the mechanisms for the effect of transformational leadership on OCB. The design of this study is a quantitative study using a survey method through distributing questionnaires to frontline employees in the hospitality industry. 250 questionnaires distributed there were 218 that can be used. By testing using the Structural Equation Model - Partial Least Square (SEM-PLS) method with SMART PLS 3, it was found that transformational leadership has no direct effect on OCB like most other Asian studies. Affective commitment and work engagement show partial mediating effects in the relationship between transformational leadership and OCB in the workplace. This study found that transformational leadership can influence OCB through the mediating effects of affective commitment and job involvement. These results are expected to enrich the psychological mechanisms that can explain the effect of transformational leadership on OCB. Future research is expected to be able to explain a more comprehensive flow of transformational leadership, affective commitment, work engagement, and OCB.